A Comparative Study of Ranging Techniques in Deep Space Applications. (January 2016) - Cong, Bo; Mao, Nanping; Tao, Xiaohong
Abstract: In this paper, main ranging techniques in deep space applications are elaborated and analyzed. Their ranging accuracy, acquisition time and complexity are compared. It is shown that the code-tone ranging method has obvious advantage over others in deep space tracking. Start your abstract here...